Synergistic biochar/hydrogel composites: A next-generation platform for sustainable water treatment - Ankit Verma; Mukesh Kumar; Pooja Puri; Humaira Parveen; Sayeed Mukhtar; Mona O. Albalawi; Sangeeta Bhogal; Rohit Jasrotia (Journal of Environmental Chemical Engineering, 2026)

Toxicity assessment of Mitragyna speciosa leaf extracts using zebrafish ( Danio rerio ) embryos and analysis of their Q-TOF LCMS chemical profiles - Taslima Begum; Qamar Uddin Ahmed; Mohd Hafiz Arzmi; ABM Helal Uddin; Syed Adnan Ali Shah; Mohd Salleh Rofiee; Humaira Parveen; Sayeed Mukhtar; Uzma Faridi; Sharifah Nurul Akilah Syed Mohamad; Alfi Khatib (Natural Product Research, 2026)

Antimicrobial and antioxidant activities of Tetracera macrophylla Hook.f. & Thomson leaf extracts: insights from Q-ToF-LCMS, pharmacokinetics and molecular docking approach - Qamar Uddin Ahmed; Muhammad Akmal Hakim Ab Rahim; Mohd Hafiz Arzmi; ABM Helal Uddin; Syed Adnan Ali Shah; Mohd Salleh Rofiee; Humaira Parveen; Sayeed Mukhtar; Uzma Faridi; Nurul Hidayah Mohd Rosedi; Murni Nazira Sarian; Taslima Begum (Natural Product Research, 2026)

Biobased materials in the circular economy: A strategic review on the advanced functionalization and applications of biopolymers - Syed Kashif Ali; Abdullah Ali Alamri; Faris Alfifi; Hassien M. Alnashiri; Humaira Parveen; Sayeed Mukhtar; Shaily; Liyaqat Ali Kamran; Mohd Waseem; Adnan Shahzaib (Journal of Environmental Chemical Engineering, 2026)

Multi-Step Synthesis, Characterization and Physicochemical Investigation of Benzylated Indole Thiosemicarbazone as Selective Switch on Sensing Properties for Copper Ion - Md. Zafer Alam; Suhail Ahmad; Md. Mohasin; Umme Salma; Alimuddin; Humaira Parveen; Sayeed Mukhtar; Salman A. Khan (Journal of Fluorescence, 2025)

A review on Mitragyna speciosa (Rubiaceae) as a prominent medicinal plant based on ethnobotany, phytochemistry and pharmacological activities - Taslima Begum; Mohd Hafiz Arzmi; Alfi Khatib; A.B.M. Helal Uddin; Maryam Aisyah Abdullah; Kamal Rullah; Siti Zaiton Mat So’ad; Nur Fatihah Zulaikha Haspi; Murni Nazira Sarian; Humaira Parveen; Sayeed Mukhtar; Qamar Uddin Ahmed (Natural Product Research, 2025)

Ultrasound-Assisted Synthesis of Chalcone: A Highly Sensitive and Selective Fluorescent Chemosensor for the Detection of Fe3+ in Aqueous Media - Salman A. Khan; Md. Zafer Alam; Md. Mohasin; Suhail Ahmad; Umme Salma; Humaira Parveen; Sayeed Mukhtar; Menier Al-Anazi; Fatimah A. Alotaibi; Mahmoud A. Abdelaziz (Journal of Fluorescence, 2024)

Sargassum wightii Aqueous Extract Improved Salt Stress Tolerance in Abelmoschus esculentus by Mediating Metabolic and Ionic Rebalance - Zawar Khan; Humaira Gul; Mamoona Rauf; Muhammad Arif; Muhammad Hamayun; Aziz Ud-Din; Zahoor Ahmad Sajid; Sheza Ayaz Khilji; Aliya Rehman; Asma Tabassum; Zahida Parveen; In-Jung Lee (Frontiers in Marine Science, 2022)
Salinity stress has hindered the growth and yield of crops globally. The demands for inducing salt stress tolerance by natural and biological sources with potent antioxidants and growth-promoting metabolites have been the main focus of the recent era. Therefore, the current research was conducted to extract salt stress tolerance-ameliorating metabolites and growth-promoting hormones from the marine brown macroalgae Sargassum wightii Greville ex J. Agardh with maximum antioxidant potential used as a liquid fertilizer for okra ( Abelmoschus esculentus L.). In the current study, the biochemical analysis showed that Sargassum aqueous extract (SAE) was rich in growth-promoting metabolites, antioxidants, and hormones. Meanwhile, overaccumulation of glycine betaine attracted the focus of the current research dealing with salt stress tolerance amelioration in A. esculentus . The plants supplemented with SAE (2% and 4%) and 0.04% ascorbic acid (AsA) alone and in combinations were subjected to sodium salt stress (NaCl; 75 mM). Results revealed that SAE efficiently promoted the vegetative and reproductive growth of plants by elevating the growth-promoting metabolites and hormones in comparison to control plants. Ionic contents (Na + , K + , Ca 2+ , and Mg 2+ ) and ratios (K + /Na + , Mg 2+ /Na + , and Ca 2+ /Na + ) were modulated in SAE-treated plants. SAE also increased the level of carbohydrates, proteins, lipids, carotenoids, and proline and decreased the level of hydrogen peroxide and abscisic acid in salt-treated plants compared with the control groups. Enzymatic activities of catalase, ascorbate peroxidase, and guaiacol peroxidase were also enhanced by SAE treatment upon salt stress. The SAE-mediated stress tolerance amelioration and the positive growth response of A. esculentus were further accelerated by AsA (0.04%) supplementation used in combination with SAE (2% and 4%). The current study revealed a novel report of the antioxidant and metabolite-rich algal extract ( S. wightii ) formulation along with AsA that induced salt stress tolerance and promoted the overall growth performance of A. esculentus by rebalancing the ionic and metabolic status.

Mechanistic Approaches of Internalization, Subcellular Trafficking, and Cytotoxicity of Nanoparticles for Targeting the Small Intestine - Asadullah Madni; Sadia Rehman; Humaira Sultan; Muhammad Muzamil Khan; Faiz Ahmad; M. Rafi Raza; Nadia Rai; Farzana Parveen (AAPS PharmSciTech, 2020)

Exogenously applied 5-aminolevulinic acid modulates growth, secondary metabolism and oxidative defense in sunflower under water deficit stress - Rizwan Rasheed; Humaira Yasmeen; Iqbal Hussain; Muhammad Iqbal; Muhammad Arslan Ashraf; Abida Parveen (Physiology and Molecular Biology of Plants, 2020)